Analisis Budaya Organisasi Dan Kinerja Dengan Pengembangan Karir Karyawan Kantor PTPN Regional 1 Medan - Simamora, Venny Chyntia; Sianturi, Charles M.; Simangunsong, Ridhon NB. (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
The purpose of this study was to determine the relationship between organizational culture values ​​and employee performance on the career development of administrative employees at the PTPN IV Regional 1 Medan City Office with an organizational culture called AKHLAK. This type of research is qualitative. The data collection method used was an open interview technique. The data analysis technique used was data reduction, data grouping, then presented in the form of descriptive narratives and then continued with drawing conclusions. The results of the study showed that the implementation of the AKHLAK organizational culture values ​​had been implemented after being socialized and evaluated periodically. Employee performance evaluation is based on the SOP and performance standards that have been set. Based on the results of the data analysis, it was concluded that the AKHLAK cultural values ​​had a positive impact on employee performance and employee performance was the basis for employee career development at the PTPN IV Regional 1 Medan City Office. Organizational Culture Values, Performance, Career Development